2003
DOI: 10.1016/j.neuroimage.2003.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Isolating the retrieval of imagined pictures during episodic memory: activation of the left precuneus and left prefrontal cortex

Abstract: The posterior medial parietal cortex and the left prefrontal cortex have both been implicated in the recollection of past episodes. In order to clarify their functional significance, we performed this functional magnetic resonance imaging study, which employed event-related source memory and item recognition retrieval of words paired with corresponding imagined or viewed pictures. Our results suggest that episodic source memory is related to a functional network including the posterior precuneus and the left l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(70 citation statements)
references
References 45 publications
2
67
0
1
Order By: Relevance
“…The precuneus seems to be involved in many imagery and mental simulation tasks (see Cavanna and Trimble (2006) for an extended review). Additionally, activity in the precuneus was also observed in LTM tasks after imaginary encoding (e.g., Fletcher et al, 1996;Lundstrom et al, 2003Lundstrom et al, , 2005Shallice et al, 1994). For this reason, Fletcher et al called this structure the 'minds eye'.…”
Section: Resultsmentioning
confidence: 99%
“…The precuneus seems to be involved in many imagery and mental simulation tasks (see Cavanna and Trimble (2006) for an extended review). Additionally, activity in the precuneus was also observed in LTM tasks after imaginary encoding (e.g., Fletcher et al, 1996;Lundstrom et al, 2003Lundstrom et al, , 2005Shallice et al, 1994). For this reason, Fletcher et al called this structure the 'minds eye'.…”
Section: Resultsmentioning
confidence: 99%
“…In imaging studies, DLPFC has been linked with numerous mnemonic and nonmnemonic functions, including LTM retrieval (Lundstrom et al, 2003;Wager & Smith, 2003;Ranganath, Johnson, & DʼEsposito, 2000;Nolde, Johnson, & DʼEsposito, 1998;Wagner, Desmond, Glover, & Gabrieli, 1998, Nyberg et al, 1995, maintenance and manipulation of items in WM (Cabeza & Nyberg, 2000), decision-making , set shifting (Zanolie et al, 2008), and task difficulty (Braver et al, 1997;Manoach et al, 1997). Perhaps most relevant to the present study are its role in search processes subserving memory retrieval and its role in WM (see DʼEsposito, 2007 for a review).…”
Section: Dissociation Of Frontal and Hippocampal Activitymentioning
confidence: 88%
“…The more positive frontal ERP deflections, when self-generated information is targeted, might indicate the activation of prefrontal brain areas involved in the retrieval of self-relevant information (Lundstrom et al, 2003;Vinogradov et al, 2008). The role prefrontal brain structures in reality monitoring is also underlined by a recent fMRI study on schizophrenia patients with auditory verbal hallucinations (Raij et al, 2009).…”
Section: Frontal Erp Effectmentioning
confidence: 98%
“…It might be tempting to speculate that the frontally distributed ERP difference reflects activation of frontal brain areas involved in the retrieval of self-generated information: Recent functional magnetic resonance imaging (fMRI) studies have indeed shown that this kind of retrieval is associated with activation of rostral medial prefrontal brain areas Vinogradov et al, 2008) and left-lateral prefrontal structures (Lundstrom et al, 2003). However, Leynes et al (2005) themselves were somewhat reluctant in interpreting their results ("it is unclear exactly what these differences signify", p. 520).…”
Section: Introductionmentioning
confidence: 99%